ON ORTHOGONAL REVERSE DERIVATIONSOF SEMIPRIME RINGS - Majeed, Abdul Rhman (Iraqi Journal of Science, 2024)
In this paper some results concerning two reverse derivations on semiprime rings are presented. These results are related to a result which is inspired by the classical result of E. Posner. This result is asserts that if R is a 2- torsion free semiprime ring, f and h are non-zero reverse derivations of R. Then f h can not be a non-zero derivation. A notion of orthogonal reverse derivations arises here.Key word and phrases: prime ring, semi-prime ring, derivation, reverse derivation, orthogonal reverse derivation.